Performance evaluation and improvement among salesmen in the Nigerian fast moving consumer goods sector - Olatunji, Olutayo Akanji; Awolusi, Olawumi Dele (Journal of Social and Development Sciences, 2020)
This study examined the impact of systematic performance evaluation on performance improvement among salesmen in the Fast Moving Consumer Goods Sector in Nigeria. This is occasioned by the peculiar nature of the job of the salesman which requires that specific attention be paid to the mode of performance evaluation deployed for them and its impact on their productivity. Using Yamane formula, convenience sampling method was used to select 263 respondents from the sales team of PZ Cussons Nigeria PLC. Four hypotheses were subsequently tested using correlation test. Based on the analysis, the study found a significant influence of clear, specific and challenging goals on the performance of salesmen in the Fast Moving Consumer Goods sector in Nigeria. It was also deduced that there is no significant influence of detailed and timely feedback on the performance of salesmen in the Fast Moving Consumer Goods sector in Nigeria. Furthermore, the study also revealed a significant influence of employee reward and recognition, as well as, training and development on the performance of salesmen in the Fast Moving Consumer Goods sector in Nigeria. Based on the findings, the study recommended a clear, complete and inspiring job requirement of all salesmen so that the employee can continuously improve performance. Furthermore, feedback from appraisal and evaluation should also inspire, encourage and motivate salesmen without including any form of threat and fear of job security. Finally, Fast Moving Consumer Goods sector in Nigeria should embark on capacity development of human resources through training and mentoring. This study therefore contributes to limited studies on performance evaluation, as well as, validation of both the conceptual and theoretical postulations in the context of Fast Moving Consumer Goods sector in Nigeria.